Ownership concentration, monitoring and optimal board structure - Clara Graziano; Annalisa Luporini (Center for Economic Studies and ifo Institute (CESifo), 2005)
The paper analyzes the optimal structure of the board of directors in a firm with a large shareholder sitting on the board. In a one-tier structure the sole board performs all tasks, while in a two-tier structure the management board is in charge of project selection and the supervisory board is in charge of monitoring. We consider the case in which the large shareholder sits on (and controls) the supervisory board but not on the management board. We show that such a two-tier structure can limit the interference of the large shareholder and can restore manager's incentive to exert effort to become informed on new investment projects without reducing the large shareholder's incentive to monitor the manager. This results in higher expected profits. The difference in profits can be sufficiently high to make the large shareholder prefer a two-tier board even if this implies that the manager selects his own preferred project. The paper has interesting policy implications since it suggests that twotier boards can be a valuable option in Continental Europe where ownership structure is concentrated. It also offers support to some recent corporate governance reforms (like the socalled Vietti reform in Italy) that have introduced the possibility to choose between one-tier and two-tier structure of boards for listed firms.
Keywords: G34; L22; 330; board of directors; dual board; corporate governance; monitoring; project choice; Corporate Governance; Eigentümerstruktur; Vorstand; Anreizvertrag; Theorie; Großaktionär